Répondre :
Réponse:
It seems like you're trying to evaluate an expression. Let's break it down step by step.
1. First, let's calculate the expression inside the parentheses: (5,2-0,3).
5.2 - 0.3 = 4.9
2. Now, let's calculate the expression inside the square brackets: (4,3 - 0,7).
4.3 - 0.7 = 3.6
3. Next, let's calculate the expression inside the second set of parentheses: 1 - (4.9 - 3.6).
4.9 - 3.6 = 1.3
1 - 1.3 = -0.3
4. Finally, let's calculate the entire expression: H = 4 - (-0.3).
4 - (-0.3) = 4 + 0.3 = 4.3
So, H = 4.3.
bonsoir;
H=4,1-(5,2-0,3)-[7,1-(4,3 - 0,7)]
= 4,1 -(4,9) -[7,1 -( 3,6)]
= 4,1 -4,9 -( 3,5)
= 4,1-4,9-3,5
= -4,3
Merci d'avoir visité notre site Web dédié à Mathématiques. Nous espérons que les informations partagées vous ont été utiles. N'hésitez pas à nous contacter si vous avez des questions ou besoin d'assistance. À bientôt, et pensez à ajouter ce site à vos favoris !